Introduction - J. Mokhoathi; L. Sutton (Acta Theologica)
The year 2020 marked the beginning of the 40th Celebration of the Faculty of Theology and Religion at the University of the Free State. The theme for the celebrations is “Transforming Theology and Religion?”. “Transforming Theology and Religion?” – The theme of the 40-year anniversary is ambiguous. With this theme, the Faculty is accentuating the fact that theology and religion are transforming. Also, in the Free State, theology and religion have in many ways contributed towards the transformation of the country and continent. It is, however, also acknowledged that theology and religion have not always actually practised this transforming potential. In fact, theology and religion have in some ways coalesced against transformation. The question mark in the theme is therefore very significant. Theology itself will have to be transformed, to form and transform. The theme of the 40-year anniversary therefore allows us to ask anew how theology and religion will have to be transformed so that we – in inter and multi-disciplinary conversation as well as in light of the many ways in which we have not actualised this – will practise our transforming potential globally and locally in accordance with this significant milestone.